Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6cp05751a
|View full text |Cite
|
Sign up to set email alerts
|

Peeling the astronomical onion

Abstract: Journal Name ARTICLEThis journal is © The Royal Society of Chemistry 20xxJ. Name., 2013, 00, 1-3 | 1 Water ice is the most abundant solid in the Universe. Understanding the formation, structure and multiplicity of physicochemical roles for water ice in the cold, dense interstellar environments in which it is predominantly observed is a crucial quest for astrochemistry as these are regions active in star and planet formation. Intuitively, we would expect the mobility of water molecules deposited or synthesised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…[74] However, Rosu-Finsen et al subsequently argued that the low-temperature endotherm is kinetic in origin and arises upon heating deep glassy states of hydrogen-disordered ice VI. [62] Consistent with the increase in volume upon hydrogen-ordering, the application of pressure suppresses the hydrogen ordering to ice XV, which then enables glassy states of ice VI to be reached at Tg(doped) along pathway (2) in Figure 4. The general effect of HCl-doping is a substantial decrease of the glass transition temperature from Tg(pure) to Tg(doped) estimated to be more than 30 K in case of ice VI.…”
Section: Stacking Disorder and Polytypism Of Ice Imentioning
confidence: 84%
See 3 more Smart Citations
“…[74] However, Rosu-Finsen et al subsequently argued that the low-temperature endotherm is kinetic in origin and arises upon heating deep glassy states of hydrogen-disordered ice VI. [62] Consistent with the increase in volume upon hydrogen-ordering, the application of pressure suppresses the hydrogen ordering to ice XV, which then enables glassy states of ice VI to be reached at Tg(doped) along pathway (2) in Figure 4. The general effect of HCl-doping is a substantial decrease of the glass transition temperature from Tg(pure) to Tg(doped) estimated to be more than 30 K in case of ice VI.…”
Section: Stacking Disorder and Polytypism Of Ice Imentioning
confidence: 84%
“…[74], Rosu-Finsen et al have shown that low-temperature endotherms can also be found for the corresponding D2O materials and neutron diffraction data of such a sample was shown to be consistent with deep glassy hydrogen-disordered ice VI. [62] These recent findings illustrate that doping with HCl does not only enable hydrogen ordering of ices V, VI and XII. If the hydrogen ordering can be suppressed, for example by the application of pressure,…”
Section: Stacking Disorder and Polytypism Of Ice Imentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies of molecular ices have used assumed values for n where experimental values are unavailable, or used values from the liquid phase. 9,10 Typical astrochemical surface science experiments employ high-vacuum (p ≈ 10 -7 mbar) 21,22 or ultra-high vacuum (UHV, p ≈ 10 -10 mbar) 7,23 and cryogenic cooling of the order of 10-30 K. [22][23][24] It is therefore questionable to assume that an ice will behave in the same way as in the liquid phase under ambient conditions. In other cases, when ices of mixed compositions were studied, a weighted average value based upon the relative contributions of each ice component was used for n. 15 However, this does not take into account interactions within the ice, and therefore the actual refractive index will vary significantly from that derived in this way.…”
Section: Introductionmentioning
confidence: 99%